(untitled) (American International Journal of Supply Chain Management, 2021)
ABSTRACT The positive relationship between economy expansion and urban population explosion in Nigeria has generated a corresponding proliferation of household solid waste in low income residential areas of the urban centres of the country. Studies have shown indiscriminate disposal of the household solid waste is rampant in the low-income residential areas and this has been a grave concern of the government at the grassroots. In spite of several institutional frameworks set up by the Local Authorities to attain proper management of the waste, the expectation and the reality are not in tandem and among the most cited reasons is that the management procedures and frameworks are not community-based. Based on the assertions of social innovation theory, this systematic review highlights and emphasizes the significance of community participation, via Community-Based Organizations preferably the Landlords Association, in ensuring the efficiency of the set up institutional frameworks in low-income residential areas, in particular.